2004
DOI: 10.1097/01.brs.0000129024.95630.57
|View full text |Cite
|
Sign up to set email alerts
|

Determining Cavitation Location During Lumbar and Thoracic Spinal Manipulation

Abstract: In the lumbar spine, SMT was accurate about half the time. However, because most procedures were associated with multiple cavitations, in most cases, at least one cavitation emanated from the target joints. In the thoracic spine, SMT appears to be more accurate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
118
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(123 citation statements)
references
References 10 publications
3
118
0
2
Order By: Relevance
“…5,18,20 The parasagittal view used in this case has been described in the literature as being used for realtime biofeedback to augment learning of volitional contraction of the lumbar multifidus. 20,40 Kiesel et al 28 reported the reliability of the parasagittal measurement (ICC 3,1 = 0.85) and (ICC 3,1 = 0.80) in asymptomatic subjects, but the SEM was not reported. The reliability results reported earlier (ICC 3,3 = 0.98; SEM, 0.094 cm) are from an ongoing clinical trial on patients with acute LBP where the average of 3 measures is being utilized.…”
Section: Rusi Considerationsmentioning
confidence: 99%
See 2 more Smart Citations
“…5,18,20 The parasagittal view used in this case has been described in the literature as being used for realtime biofeedback to augment learning of volitional contraction of the lumbar multifidus. 20,40 Kiesel et al 28 reported the reliability of the parasagittal measurement (ICC 3,1 = 0.85) and (ICC 3,1 = 0.80) in asymptomatic subjects, but the SEM was not reported. The reliability results reported earlier (ICC 3,3 = 0.98; SEM, 0.094 cm) are from an ongoing clinical trial on patients with acute LBP where the average of 3 measures is being utilized.…”
Section: Rusi Considerationsmentioning
confidence: 99%
“…2, 40 Ross et al, 40 utilizing accelerometers secured to the skin, reported an accuracy rate of only 46% when attempting to target a specific lumbar segment with manipulation. He also reported an average error from target of 1 vertebral segment and concluded that manipulation in the lumbar spine is generally not accurate.…”
Section: Manipulation Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are legitimate grounds to question this assumption, as I did when in 2001 I asked the following question: "If, as so many have said, a good treatment outcome depends on an accurate diagnosis, then how can we explain fairly uniformly good outcomes, given huge variation in diagnostic inputs?" 55 In addition to the problems we have seen in achieving diagnostic specificity, there are similar problems in staking claim to treatment specificity, as exemplified in the works of Ross et al 56,57 These investigators showed that cavitations during manipulation are often multiple and may occur at spinal locations other than where the segmental contact is applied. Perle and Kawchuck 58 and Perle 59 have also effectively weighed in on the issue and likelihood of adjustive specificity.…”
Section: Limitations Of This Commentarymentioning
confidence: 94%
“…During the manipulative procedure there is often a "cracking" sound signifying successful cavitation of the joint (Herzog et al, 1993a;Herzog et al, 1997;Ross et al, 2004;Pickar & Kang, 2006). Cavitation is theorized to be the result of the formation of vapor and gas bubbles within the synovial fluid upon quick separation of the joint.…”
Section: Introductionmentioning
confidence: 99%